2013
DOI: 10.5539/ass.v9n10p43
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Age and Teaching Experiences Differences in Decision-Making Behaviours of Members of Selected Kenyan Secondary School Disciplinary Panels

Abstract: The study investigated gender, age and teaching experiences differences in decision-making behaviours of members of selected Kenyan secondary school disciplinary panels.Mixed Methods design was adopted for the study. Both quantitative and qualitative data were collected. Study sample comprised 78 participants drawn from ten secondary school disciplinary panels. Participants comprised 45 males and 33 females, clustered into four age groups of-29 years (n=21), 30-39 years (n=28), 40-49 years (n=14), and 50-59 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Ünal and Ünal (2012) found that older teachers (age 45 years or more) are more active in teaching and better in classroom management skills as compared to younger teachers in high school; the more you teach, the more you acquire skills and bring improvement in the methodology of teaching. This view is buttressed by Aloka and Bojuwoye (2013) and they found that newly appointed teachers regularly end up making additional risky decisions and do not examine the background carefully when dealing with students' disciplinary snags due to the lack of experience, irresponsibility and immaturity as compared to older teachers. Putman (2012) confirmed that the more years of teaching experience teachers have, the more advanced is the level of their self-efficacies to involve students and manage the classroom.…”
Section: Teachers' Experience and Performancementioning
confidence: 99%
“…Ünal and Ünal (2012) found that older teachers (age 45 years or more) are more active in teaching and better in classroom management skills as compared to younger teachers in high school; the more you teach, the more you acquire skills and bring improvement in the methodology of teaching. This view is buttressed by Aloka and Bojuwoye (2013) and they found that newly appointed teachers regularly end up making additional risky decisions and do not examine the background carefully when dealing with students' disciplinary snags due to the lack of experience, irresponsibility and immaturity as compared to older teachers. Putman (2012) confirmed that the more years of teaching experience teachers have, the more advanced is the level of their self-efficacies to involve students and manage the classroom.…”
Section: Teachers' Experience and Performancementioning
confidence: 99%
“…Within Kenyan secondary schools, each disciplinary panel operates as a small social group to make decisions on the management o f an array o f student disciplinary or behaviour problems such as bullying, vandalism, stealing, alcohol and drug abuse, truancy, and non-com pletion o f hom ework assignments and other forms o f problem behaviours (Aloka, 2012;Aloka & Bojuwoye, 2013 ). Based on the information available during disciplinary hearings, disciplinary panel members come to a group decision leading to recom m endations on how best to manage student behaviour problems.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the various maladaptive behaviours found among Kenyan school children include bullying, vandalism, stealing, alcohol and drug abuse, truancy, not completing homework assignments and other forms of problem behaviours (Aloka & Bojuwoye, 2013). These problem behaviours impact negatively on the teaching and learning enterprises of schools as well as on the safety and security of the school environment (Aloka, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These terms of references guide the panel members' behaviours including the roles and responsibilities members are to play in order for the panel to accomplish what is expected of it. The terms of reference for the disciplinary panel serve as goals which guide members' behaviours in terms of roles and responsibilities leading to decisions of the panel (Aloka & Bojuwoye, 2013). The immediate goal is to provide appropriate response to student disciplinary problems being treated by the panel.…”
Section: Introductionmentioning
confidence: 99%